Hidroformilação do oleato de metila catalisada por complexos de ródio - Ana Nery Furlan Mendes (Química Nova, 2012)
In this work, we describe the hydroformylation of methyl oleate catalyzed by several rhodium complexes. Parameters including total pressure, phosphorous/rhodium and CO/H2 ratio, temperature and phosphorous ligands were scanned. Total conversion of the starting double bonds was achieved while maintaining excellent selectivity in aldehydes.